To take, place and refuse accountability: how team members handle tasks and roles in collaboration on school attendance problems. - Mossberg, Linda (Journal of Social Work Practice, 2025)
Role and task definition are central to collaboration in teams. However, accountability to roles and tasks has not been studied, nor how they are handled in interaction. This paper studies how members of multi-professional teams show accountability in handling roles and tasks in collaboration. Twenty meetings of two teams in a multi-professional project aimed at school attendance problems were analysed. Findings showed that members took, placed and refused formal and informal accountability to handle roles and tasks in the project. In these results, what collaboration should entail and how it should be performed was manifested through formal and informal accountability, respectively. Thus, findings show the complexity behind the prompt to define roles and tasks in collaboration by looking at interactions among members and how that shapes collaboration.